Women's access to sexual and reproductive health services and information in Ismailia, Egypt - Reem Elsayed; Wanga Zembe-Mkabile (BMC, 2024)
Abstract Background Sexual and reproductive health (SRH) is a right that should be guaranteed to every woman worldwide in order to have a healthy and safe sex life. In most Arab countries, including Egypt, there are different cultural, political, and religious factors that have contributed significantly to how society views and treats women's bodies and sexuality. As a result, it is difficult to provide solid data and information to guide policymakers, policies, and to implement awareness and preventive programmes. This study sought to address this gap by looking at the intersectionality of women's access to SRH services and information in Ismailia, Egypt. Methods The study utilised qualitative research methods. Semi-structured interviews were conducted with twelve married women and two key informant interviews with health professionals (a gynecologist and a pharmacist) in the study area. Results The study revealed that married women suffer from scarcity of understanding and knowledge of their SRH and lack of access to adequate SRH services and information. Married women's experiences of accessing SRH services and information were influenced by intersecting factors located at the micro and macro levels. These intersected factors (e.g., power dynamics, socioeconomic factors, cultural norms, and religious misconception) shaped oppression and privilege structures which created unequal access to SRH information and services. Conclusion There is a need for building quality parental relationships for women before and after marriage in order to promote positive SRH attitudes and behavior. There is an urgent need to empower women before and after marriage with accurate, safe, and affordable SRH services and information that could have life-long benefits to protect them. There is a need to conduct educational programmes, and initiate media awareness campaigns, to equip women with information and knowledge about their SRH services and information.